An experimental study of performance, combustion and emissions characteristics of an ethanol HCCI engine using water injection. (5th March 2022) - Telli, G.D.; Zulian, G.Y.; Lanzanova, T.D.M.; Martins, M.E.S.; Rocha, L.A.O.
Highlights: Water was injected in an ethanol HCCI cyl. from a converted 3-cyl. diesel engine. HCCI combustion was attained via total recirculation of exhaust gases from a CDC. Water injection can be used as a combustion phasing control to expand CAI load. Water injection improved the maximum load achievable in CAI conditions three times. The highest indicated efficiency was 39% at 6.0 bar of IMEP. Abstract: Homogeneous charge compression ignition (HCCI), also known as Controlled Auto-Ignition (CAI), enables combustion with high fuel conversion efficiency and low NOX emissions. It can benefit both spark and compression ignition engines and lessens the demand for expensive exhaust after-treatment systems. However, the HCCI application is restricted due to a limited operating range. Water injection can tackle this problem, which enables higher loads without excessive heat release rates. Although already reported in spark-ignited engines, water injection is still a novelty for HCCI combustion. The water injection strategy is not fully developed for HCCI engines, especially fueled with renewable fuels and using different methods to achieve CAI conditions. Hence, this paper studied the performance, combustion, and emissions characteristics of an ethanol HCCI engine using water injection and total exhaust gas recycling from an adjacent diesel cylinder. HCCI combustion was attained via direct recirculation of exhaust gases from a diesel cylinder, serving as a heat and active radical source for the ethanol charge auto-ignition. Water injection was used for combustion phasing control and load expansion. Detailed combustion and heat release analyses were performed. During the experiments, combustion phasing (CA50) ranged from 2 to 8 crank angle degrees (CAD) ATDC. Water injection reduced the heat release rates and prevented knock, keeping the in-cylinder temperatures below 1850 K. The results indicated that water injection effectively controlled combustion phasing and heat release rate, increasing the maximum operational load threefold. The combustion duration increased with water injection, varying from 6.6 CAD at high loads to 17.0 CAD at low loads. The indicated conversion efficiency was 27% at low loads and achieved the maximum of 39% at 6 bar of indicated mean effective pressure (IMEP). The NOX emissions formed in ethanol HCCI combustion were lower than 0.8 g/kWh.